Using water chemistry to define ecological preferences within the moss genus Scorpidium, from Wales, UK. (3rd July 2019) - Graham, Jonathan; Farr, Gareth; Hedenäs, Lars; Devez, Aurelie; Watts, Michael J.
ABSTRACT: Introduction: Three Scorpidium species: S. scorpioides, S. cossonii and S. revolvens are often associated with habitats of high conservation value. This is the first attempt to define the chemical niches for these Scorpidium species in Wales (UK) and allows us to compare these with earlier European datasets. Methods: Water chemistry from sixteen locations was analysed using water obtained by direct squeezing of mosses sampled from a total of 77 spots, and their principal water supply, e.g. springs and seepages. Key Results: Statistical analysis by spherical k-means clustering suggests there are two distinct groups in the dataset; one characterised by S. cossonii and another by S. revolvens, associated with differences in pH and Electric Conductivity (EC) of the habitat. The Welsh habitats have higher pH and EC than Scandinavian habitats of the species, which could potentially be a result of different pollution histories or species compositions of the areas, the latter leading to different realised niches along the mineral poor to rich gradient. Conclusions: It is hoped that with this data a better understanding of the chemical niches will support site managers and environmental regulators to make evidence-based decisions to protect these species and their habitats.